Chemistry Building, University of Washington, Seattle, approximately 1918 - Linkletter, L.G.
Built in 1908 as the art museum and Fine Arts Building for the Alaska Yukon Pacific Exposition, the building was used as a chemistry building after the fair and renamed Bagley Hall. It was remodeled in 1937 and was renamed the Physiology Hall. Around 1950 the name was changed again to the Architecture Hall. Caption on image: Chemistry Building. University of Washington. L.G. Linkletter. PH Coll 95.3 L.G. Linkletter worked as a photographer in the University District from 1906 till his death in 1937. He photographed many University events, buildings and students and was also known for his images of Mount Rainier National Park.